2021
DOI: 10.1016/j.xphs.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

A review of Formulations of Commercially Available Antibodies

Abstract: the most at 17 each. A total of 136 products were identified of which 36 are lyophilized powders and 100 are solutions. The routes of administration are mainly subcutaneous or intravenous infusion with three intravenous bolus, two intravitreal, and one intramuscular. The subcutaneous products are ready-to-use solutions or reconstituted lyophilized powders that do not require dilution while most intravenous products are concentrates that require dilution into saline or another intravenous fluid prior to infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 31 publications
(39 reference statements)
4
107
0
4
Order By: Relevance
“…Consistent with our observation, Robert Strickley and William Lambert suggested this year (2021) in their review article that “a typical subcutaneous solution formulation has 100 mg/mL antibody, sucrose at 50 mg/mL, buffered at pH 6 by 0.01M histidine, has the surfactant polysorbate 80 at 0.01 mg/mL, the viscosity lowered with 10 mg/mL arginine, and is packaged in a prefilled syringe” ( 9 ).…”
Section: Discussion and Perspectivessupporting
confidence: 76%
See 3 more Smart Citations
“…Consistent with our observation, Robert Strickley and William Lambert suggested this year (2021) in their review article that “a typical subcutaneous solution formulation has 100 mg/mL antibody, sucrose at 50 mg/mL, buffered at pH 6 by 0.01M histidine, has the surfactant polysorbate 80 at 0.01 mg/mL, the viscosity lowered with 10 mg/mL arginine, and is packaged in a prefilled syringe” ( 9 ).…”
Section: Discussion and Perspectivessupporting
confidence: 76%
“…In fact, multiple literatures as well as our formulation excipient analysis in Fig. 2 consistently concluded that arginine is the most widely used viscosity-lowering excipient because it may reduce both electrostatic interaction and hydrophobic interaction between protein molecules ( 9 , 30 , 35 ).…”
Section: Discussion and Perspectivessupporting
confidence: 55%
See 2 more Smart Citations
“…FDA has approved many monoclonal antibodies to be available commercially [ 31 ]. Margetuximab , a drug that is used in conjunction with chemotherapy to treat patients with HER2-positive metastatic breast cancer, was approved in the year 2020 [ 15 ].…”
Section: Main Textmentioning
confidence: 99%